A perceção da escola e do trabalho em crianças de jardim de infância e suas mães - Gouveia, Márcia; Cardoso, Paulo (Revista Portuguesa de Psicologia, 2015)
This study analyses the perception of school and work in kindergarten children and their mothers. Differences between urban and rural participants were also studied. The sample included 23 children (3 to 6 years old), 12 girls and 11 boys and their mothers, attending public kindergarten in rural and urban areas of Alentejo. Participants’ answers to a semistructured interview script (one for the children and another for the mothers) were analyzed according to the Consensual Qualitative Research approach. Results reveal that children perceive school as a place of learning and socializing, while work is perceived as a means to both obtain economic support, and to produce and acquire goods. The perception of school as a place for socialization is significantly more frequent among rural children than among urban ones. Mothers’ perception of school and work is similar to their children’s perception. This result suggests family influence on the way children perceive school and work. Results are discussed considering their limitations and practical implications.
Keywords: School; Work; Career Development; Family